Metaphors in Swedish journalism: the language of business - Mikołajczyk, Magdalena (Folia Scandinavica Posnaniensia, 2007)
This paper discusses metaphors from the standpoint of cognitive semantics and explores conceptual metaphors in the Swedish language of business, as present in the joumalistic language of everyday newspapers. The introduction briefly reviews the history of metaphorical research, foUowed by a selection of conceptual metaphors found in the economic articles of two Swedish dailies 'Dagens Nyheter' and 'GOteborgs Posten'. This paper also analyses the functions performed by metaphors in economic articles.